The Role of Operator Training Simulator to Sustain XYZ Plant Performance in Digital Era - Made Mariana (CV Media Inti Teknologi, 2026)
Background: In digital and highly dynamic business contexts, sustainable performances are essential to meet customer’s expectation and to keep plant running smoothly and safely. However, many companies still adopted traditional training methods which are not sufficient enough to develop talent to reach expected competency level. XYZ plant faces multiple challenges to maintain its performance, yet continues to strain to speed-up talent development by adopting Operator Training Simulator (OTS) – high-fidelity digital imitation of real process plant.Aims: This study aims to evaluate the role of OTS in sustaining XYZ plant performance and how the learnings can be documented and accessed readily by employees.Methods: A case study uses a quantitative approach with a descriptive method was adopted in this research. Data were collected through quantitative direct observation to gain data on actual training sessions and document analysis related to OTS and plant performance.Result: The findings show that despite from high dynamic business environments particularly manpower disturbances, the OTS support the company to develop its talent by enabling experienced-based learning to operate the plant in several scenarios and handling emergency situation in a free risk context, test and certify operator, and support the plant knowledge management system improvement. OTS application enhanced the employee knowledge and skills including problem-solving skills, emergency handling skills and communication skills.Conclusion: The study concludes that OTS plays a critical role in sustaining plant performance by developing talent to reach its designed competency, improving knowledge preservation and information management, contributing to digital knowledge repositories, and learning archives.